Pengembangan Model Contextual Teaching and Learning (CTL) Pada Pembelajaran Seni Musik Kelas 4 SD - Dinda Ayu Pramuningtyas (Universitas Sebelas Maret, 2025)
AbstractMusic learning in elementary schools generally still uses learning models that are less effective and memorable for students. Therefore, this research was made to improve the ability of students to think critically through learning the art of music in elementary schools through the development of learning models for arts and crafts subjects (especially in learning the art of music). The researchers specifically targeted the objectives to be achieved as follows: (1) Identification of problems that occur in learning music in elementary schools; (2) Identification of the needs needed in learning the art of music in elementary schools, especially during the covid-19 pandemic; (3) describes the process of learning the art of music in elementary schools using the Contextual Teaching and Learning (CTL) model. In this study, the researchers used the Research and Development (R&D) method to be able to develop a Contextual Teaching and Learning (CTL) learning model which would later determine whether the CTL learning method was effectively used in learning the art of music at the elementary level. Keywords: music art, contextual, critical thinking, elementary school, develop AbstrakPembelajaran seni musik di Sekolah Dasar umumnya masih menggunakan model pembelajaran yang kurang efektif dan terkesan kurang bermakna bagi para peserta didik. Maka dari itu, penelitian ini dibuat guna meningkatkan kemampuan peserta didik dalam berpikir kritis melalui pembelajaran seni musik di Sekolah Dasar melalui pengembangan model pembelajaran pada mata pelajaran seni budaya dan prakarya (khususnya pada pembelajaran seni musik). Adapun peneliti menargetkan secara khusus tujuan yang ingin dicapai adalah sebagai berikut: (1) mengidentifikasi permasalahan yang terjadi dalam pembelajaran seni musik di Sekolah Dasar; (2) mengidentifikasi kebutuhan yang diperlukan dalam pembelajaran seni musik di SD khususnya di masa pandemi covid-19; (3) menjabarkan proses pembelajaran seni musik di SD dengan menggunakan model Contextual Teaching and Learning (CTL). Dalam penelitian ini peneliti menggunakan metode Research and Development (R&D) untuk dapat mengembangkan model pembelajaran Contextual Teaching and Learning (CTL) yang nantinya akan menentukan apakah metode pembelajaran CTL ini efektif bila digunakan dalam pembelajaran seni musik di tingkat SD. Kata kunci: seni musik, Contextual, berpikir kritis, sekolah dasar, mengembangkan